Climate and Energy Policy in Hungary - Maria Csete; Janos Szlavik (Energies, 2012)
The energy problem has been redefined as one of the most important elements of sustainable development by climate change, adaptation and mitigation. Meeting energy needs is always a current issue in Hungary, irrespective of climate change because of the country’s high dependency on oil and gas imports, limited opportunities to replace them with domestic production, and the pollution associated with using fossil energy sources. Increasing effectiveness and saving energy can provide relatively short-term solutions with bearable costs and a relatively quick return on investment. The aim of the present paper is to give an overview about the climate and energy policy in Hungary with a special focus on the new energy strategy. Energy policy has a pivotal role in the economic recovery plan of the Hungarian government. The National Energy Strategy 2030 taking shape in Hungary takes climate policy into account with respect to adaptation and mitigation and lists renewable energy sources as the second most important tool for achieving strategic goals. As in most countries, it is also possible in Hungary to introduce climate strategy measures with zero social costs. The expedient management of climate change requires the combination of prevention, adaptation and dissemination initiatives. Strategies must meet a dual requirement: they must face the economic risks associated with premature measures, while also considering the adverse effects of delay.